A (im)penhorabilidade da verba salarial para pagamentos de dívida não alimentares - Birkhan Filho, Paulo Roberto (2024)
This article aims to study in all areas the ways in which salary funds can be seized to pay non-food debts. We know that judicial protections need to be fulfilled effectively, to this end we look at the existential minimum necessary for the survival of families as well as the effective compliance and total satisfaction of the creditor. We will seek, in a concrete and in-depth way, in the doctrine, judged and mainly in recent jurisprudence, the effective ways to guarantee the protected asset of the creditor. We do not forget to delve into the social and fundamental universe, as we need to guarantee, in addition to the above, also the dignity of families in surviving fairly, maintaining their existential minimum as well as the proportionality of such constrictive measures.